Alpha 2-adrenoreceptor stimulation does not inhibit L-type calcium channels in mouse pancreatic beta-cells. - Bokvist, K; Ammälä, C; Berggren, P; Rorsman, P; Wåhlander, K (1991)
The effects of alpha 2-adrenergic stimulation on the Ca(2+)-current in mouse pancreatic beta-cells were investigated using the patch-clamp technique. When using the conventional whole-cell recording configuration (dialysis of cell interior with pipette solution), addition of adrenaline (1 microM) or the alpha 2-adrenergic agonist clonidine (5 microM) failed to reduce the Ca(2+)-current, irrespective of whether intracellular GTP (or GTP gamma S) was present or not and at both physiological (1.3 mM) and elevated (10.2 mM) Ca(2+)-concentrations. In fact, in the absence of added guanine nucleotides, the agonists tended to increase the Ca(2+)-current amplitude in the presence of the higher Ca(2+)-concentration. Ca(2+)-channel activation measured at 1.3 mM Ca2+ was not affected by clonidine. Half-maximal activation was observed at approximately -20 mV. In addition, when Ca(2+)-currents were recorded from intact beta-cells, using the perforated patch whole-cell configuration, clonidine (1 microM) also failed to detectably affect the Ca(2+)-current. It is therefore suggested that the inhibition of beta-cell electrical activity and insulin-secretion produced by alpha 2-adrenoreceptor stimulation does not result from suppression of the L-type Ca(2+)-current.